Migration and development at home: Bitter or sweet return? Evidence from Poland. (January 2018) - Coniglio, Nicola Daniele; Brzozowski, Jan
The existing economic literature focuses on the benefits that return migrants offer to their home country in terms of entrepreneurship and human and financial capital accumulation. However, return migration can have modest or even some detrimental effects if the migration experience was unsuccessful and/or if the migrant fails to re-integrate into the home country's economy. In our paper, we empirically show which factors – both individual characteristics and features related to the migration experience – influence the likelihood of a sub-optimal employment of returnees' human capital employing an original dataset on a representative sample of return migrants in Silesia (Poland).